Fast and Easy Synthesis of Silver, Copper, and Bimetallic Nanoparticles on Cellulose Paper Assisted by Ultrasound - Zúñiga-Loyola, C; Zúñiga-Loyola, C (Elsevier B.V., 2023)
This work focuses on a systematic method to produce Ag, Cu, and Ag/Cu metallic nanoparticles (MNPs) in situ assisted with ultrasound on cellulose paper. By tuning the concentration of AgNO3 and CuSO4 salt precursors and ultrasound time, combined with a fixed concentration of ascorbic acid (AA) as a reducing agent, it was possible to control the size, morphology, and polydispersity of the resulting MNPs on cellulose papers. Notably, high yield and low polydispersity of MNPs and bimetallic nanoparticles are achieved by increasing the sonication time on paper samples pre-treated with salt precursors before reduction with AA. Moreover, mechanical analysis on paper samples presenting well-dispersed and distributed MNPs showed slightly decreasing values of Young s modulus compared to neat papers. The strain at break is substantially improved in papers containing solely Ag or Cu MNPs. The latter suggests that the elastic/plastic transition and deformation of papers are tuned by cellulose and MNPs interfacial interaction, as indicated by mechanical analysis. The proposed method provides insights into each factor affecting the sonochemistry in situ synthesis of MNPs on cellulose papers. In addition, it offers a straightforward alternative to scale up the production of MNPs on paper, ensuring an eco-friendly method. © 2023